Serogrouping and Molecular Characterization of ESBL-Producing Avian Pathogenic Escherichia coli from Broilers and Turkeys with Colibacillosis in Algeria - Nadia Safia Chenouf; Chafik Redha Messaï; Isabel Carvalho; Tamara Álvarez-Gómez; Vanessa Silva; Abdelghani Zitouni; Ahcene Hakem; Patricia Poeta; Carmen Torres (Antibiotics)
Avian colibacillosis caused by avian pathogenic Escherichia coli (APEC) strains is a bacterial disease responsible for enormous economic losses in the poultry industry, due to high mortality rates in farms, antibiotic therapy costs, and seizures at slaughterhouses. The aim of this study was to characterize the serogroups and molecular features of extended spectrum β-lactamase (ESBL)-producing APEC isolates recovered from 248 liver samples of 215 broilers and 33 turkeys with colibacillosis lesions in northeast Algeria. For this, microbiological tests were carried out, according to the recommended standards: E. coli isolates were recovered using standard microbiological protocols, and identification was carried out by MALDI-TOF MS. Serogrouping was performed using a rapid agglutination slide and the antisera of three O somatic groups (O1, O2, O78). Antimicrobial susceptibility was determined by the disk diffusion method. PCR assays and sequencing were used to detect antimicrobial resistance genes, integrons, phylogrouping, and MLST. Conjugation experiments were also conducted to determine the transferability of the retrieved ESBL-encoding genes. Overall, 211 (85.1%) APEC isolates were collected (one per positive sample), and 164 (77.7%) of them were typable. The O2 and O1 serogroups were the most detected (46.1% in broiler typable isolates and 61.5% in turkey typable isolates). Seventeen APEC isolates were ESBL-producers and harbored the following genes (number of isolates): blaCTX-M-1 (14), blaCTX-M-15 (2), and blaSHV-12 (1). They belonged to phylogroups D (10 isolates), B1 (6 isolates), and B2 (1 isolate). The MLST of 13 ESBL producers revealed seven STs: ST23, ST38, ST48, ST117, ST131, ST1146, and ST5087. The ESBL-encoding genes were transferred by conjugation among 15 ESBL-producing isolates, and transconjugants acquired either the IncK or IncI1 plasmids. Concerted efforts from all poultry actors are needed to establish surveillance monitoring strategies to mitigate the spread of ESBL-producing isolates implicated in avian colibacillosis.